A Call for Evaluation of Restorative Justice Programs. (January 2021) - Gang, Daye; Loff, Bebe; Naylor, Bronwyn; Kirkman, Maggie
Restorative justice as a response to sexual violence continues to be subject to significant criticism. To assess the evidence, we sought to appraise and synthesize evaluations of restorative justice programs for sexual and family violence offences by conducting a systematic review of peer-reviewed literature. However, our rigorous search identified only one eligible study. This dearth of evidence leaves us unable to identify how best to achieve the aims for which programs were established and poses difficulties for policy makers determining whether it is justified to introduce restorative justice programs for sexual and family violence. We recommend that evaluations of restorative justice programs that accept sexual and family violence cases be conducted as a matter of urgency.